119k views
0 votes
Please Help!!!! I really need this FAST

Please Help!!!! I really need this FAST-example-1
User ILevi
by
5.5k points

2 Answers

6 votes

Answer:

A

Explanation:

Let's solve your equation step-by-step.

7x−4+8x=6x+8

Step 1: Simplify both sides of the equation.

7x−4+8x=6x+8

7x+−4+8x=6x+8

(7x+8x)+(−4)=6x+8(Combine Like Terms)

15x+−4=6x+8

15x−4=6x+8

Step 2: Subtract 6x from both sides.

15x−4−6x=6x+8−6x

9x−4=8

Step 3: Add 4 to both sides.

9x−4+4=8+4

9x=12

Step 4: Divide both sides by 9.

9x9=129

x=43

User Vygintas B
by
5.8k points
5 votes

Answer:

B) x = 4/3

Explanation:

7x - 4 +8x = 6x + 8

7x + 8x - 6x = 8 + 4

7x + 2x = 12

9x = 12

x = 12 / 9

x = 4/3 ( got this answer by giving by 3rd table)

User Angel Hadzhiev
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.